Catch me - Gardner, Lisa. (New York : Dutton, 2012)
A police dispatcher seeks out Boston Sgt. Det. D.D. Warren Grant and asks him to investigate her expected murder. Meanwhile, Warren is looking into the slayings of two pedophiles with the assistance of a female rookie sex crime detective.
Keywords: Warren, D. D. (Fictitious character) -- Fiction; Murder -- Investigation -- Fiction; Boston (Mass.) -- Fiction; Mystery fiction